2019
DOI: 10.1002/cncr.32637
|View full text |Cite
|
Sign up to set email alerts
|

Communication during childhood cancer: Systematic review of patient perspectives

Abstract: Effective communication is challenging in childhood cancer, where decisions carry unpredictable and life-threatening implications. We aimed to describe patients' experiences of communicating with clinicians during treatment of childhood cancer. A systematic review of qualitative studies to April 2019 was performed. Eligible studies included patients diagnosed with cancer at age ≤ 18 years and reported their perspectives of communicating with clinicians during treatment of childhood cancer. Data were extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 143 publications
(267 reference statements)
6
69
0
14
Order By: Relevance
“…For example, variability in caregivers' desired level of involvement in decision making appeared to be influenced by the role of women in a family. Included studies also highlighted different levels of involvement of children in information exchange, and this was consistent with a recent review that suggested cultural values affect pediatric patient inclusion in diagnostic communication 61 . Some of the reviewed studies described distant caregiver‐provider relationships and a hierarchical medical culture, which may reflect differences in the extent to which providers embrace principles of patient‐ or family‐centered communication.…”
Section: Discussionsupporting
confidence: 67%
“…For example, variability in caregivers' desired level of involvement in decision making appeared to be influenced by the role of women in a family. Included studies also highlighted different levels of involvement of children in information exchange, and this was consistent with a recent review that suggested cultural values affect pediatric patient inclusion in diagnostic communication 61 . Some of the reviewed studies described distant caregiver‐provider relationships and a hierarchical medical culture, which may reflect differences in the extent to which providers embrace principles of patient‐ or family‐centered communication.…”
Section: Discussionsupporting
confidence: 67%
“…Studies show that ill children experience distress associated with the illness; for example, side effects of treatment and feelings of loneliness, isolation, and powerlessness 1 . They also report feeling disempowered due to a lack of information and being neglected by clinicians who do not have time to talk or answer questions 2 . Early physical and emotional distress has been found to predict long‐term suffering among these children, which suggests that implementation of family interventions could reduce the risk of suffering in children with cancer 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The child is a spectator "of the hushed whispers and discussions among grown-ups and can ascertain that a secret exists that is not to be discussed" (Sisk et al 2016;Claflin and Barbarin 1991;Coyne et al 2016;Cole and Kodish 2013, p. 641;Bluebond-Langer 1980;Lin et al 2019). Children know when something is wrong (Wangmo et al 2016).…”
Section: P3 Descr : Disclosing Prognostic Information To the Child Against Parental Wish Will Further Destabilize The Family Unitmentioning
confidence: 99%
“…Thirdly, the child (and the family) benefits from disclosing information. For example, it provides the opportunity to develop their decisional capacity (Lin et al 2019), it causes children to value more strongly their treatment (Fukuda and Fukuda 2018), it promotes the therapeutic relationship and compliance with treatment recommendations (Hudson et al 2019;Slavin et al 1982), it gives the child some control over the situation and a validation of the experience (Lin et al 2019;Kunin 1997), it fosters trust in the physician (Lin et al 2019;Kunin 1997; American Academy of Pediatrics 1995), it improves a child's well-being (Bluebond-Langer 1980; Hudson et al 2019), it generally increases the likelihood of children approaching their parents for information (LePoire 2006), and it empowers children by enhancing their assertive agency (Lin et al 2019).…”
Section: P3 Descr : Disclosing Prognostic Information To the Child Against Parental Wish Will Further Destabilize The Family Unitmentioning
confidence: 99%